Glutamyl‐prolyl‐tRNA synthetase induces fibrotic extracellular matrix via both transcriptional and translational mechanisms. Issue 3 (28th December 2018) - Song, Dae-Geun; Kim, Doyeun; Jung, Jae Woo; Nam, Seo Hee; Kim, Ji Eon; Kim, Hye-Jin; Kim, Jong Hyun; Lee, Seo-Jin; Pan, Cheol-Ho; Kim, Sunghoon; Lee, Jung Weon
ABSTRACT: Fibrosis is characterized by the increased accumulation of extracellular matrix (ECM), which drives abnormal cell proliferation and progressive organ dysfunction in many inflammatory and metabolic diseases. Studies have shown that halofuginone, a racemic halogenated derivative, inhibits glutamyl‐prolyl‐transfer RNA‐synthetase (EPRS)‐mediated fibrosis. However, the mechanism by which this occurs is unclear. We explored the mechanistic aspects of how EPRS could develop liver fibrotic phenotypes in cells and animal models. Treatment with TGF‐β1 up‐regulated fibronectin and collagen I levels in LX2 hepatic stellate cells. This effect was inhibited in prolyl‐transfer RNA synthetase (PRS)‐suppressed LX2 cells. Using the promoter luciferase assay, TGF‐β1–mediated collagen I, α1 chain transcription and γ2 basal laminin transcription in LX2 cells were down‐regulated by EPRS suppression, suggesting that EPRS may play roles in ECM production at transcriptional levels. Furthermore, signal transducer and activator of transcription (STAT) signaling activation was involved in the effects of TGF‐β1 on ECM expression in a PRS‐dependent manner. This was mediated via a protein‐protein complex formation consisting of TGF‐β1 receptor, EPRS, Janus kinases, and STAT6. Additionally, ECM expression in fibrotic livers overlapped with EPRS expression along fibrotic septa regions and was positively correlated with STAT6 activation in carbon tetrachloride‐treated mice. This was less obvious in livers of Eprs −/+ mice. These findings suggest that, during fibrosis development, EPRS plays roles in nontranslational processes of ECM expression via intracellular signaling regulation upon TGF‐β1 stimulation.—Song, D.‐G., Kim, D., Jung, J. W., Nam, S. H., Kim, J. E., Kim, H.‐J., Kim, J. H., Lee, S.‐J., Pan, C.‐H., Kim, S., Lee, J. W. Glutamyl‐prolyl‐tRNA synthetase induces fibrotic extracellular matrix via both transcriptional and translational mechanisms. FASEB J. 33, 4341–4354 (2019). www.fasebj.org